REVIEW OF THE CURRENT STATUS OF STUDY OXYTROPIS - A Sh, Amirkhanova; G O, Ustenova (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â The use of plants for medical purposes has been known since ancient times, and despite progress in the synthesis of medicinal products, herbal remedies continue to occupy a significant place in modern medicine. As promising sources of biologically active substances of natural origin, attention is attracted by representatives of the domestic flora from the family Fabaceae. The article gives an analysis of the current state of the study of the genus of Oxytropis and shows the prospects for their comprehensive study. Work in the herbarium fund of the Institute with a collection of species of Oxytropis glabra Lam. DC. allowed to identify the presence of at least 10 herbarium sheets. While analyzing the internet sources, we collected materials on the genus and species of Oxytropis which have been investigated for many years. When analyzing internet resources, it was established that the widely used traditional Tibetan, Chinese, Mongolian, and Buryat medicine should include representatives of the genus Oxytropis (DC.) of the family Fabaceae (L.).We have studied the species of the Oxytropis and compiled a table on their chemical composition and pharmacological action.